Bank jako uczestnik kanału dystrybucji usług ubezpieczeniowych - Kufel-Siemińska, Anna (Bank as a Participant in Distribution Channel of Insurance Services, 2008)
Participation of a bank in distribution of insurance services is one of many grounds of the co--operation between banks and insurance companies, named as "bancassurance". The purpose of this study is to explain forms of banks' participation in distribution channels of insurance services. The reasons for undertaking the problem is divergence of information concerning actual participation of banks in distribution of insurance services, which appears to have its source in identification and further in considering the participation of a bank in the channel on different and as a rule not all levels. Because bank participates in distribution channel of insurance services on all of its levels: on the level of insurer, on the level of insurance agent, and on the level of insured person. The participation of a bank on all of mentioned levels allows providing the insurance service, but in the case of a bank, this participation as a rule is limited to actions related to conclusion of insurance contract.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2008; nr 1197, s. 174-180